Adaptive control method for path tracking of wheeled mobile robot considering parameter changes. (1st January 2012) - Wang, Yina; Wang, Shuoyu; Tan, Renpeng; Jiang, Yinlai
Wheeled mobile robots are widely used in industry, agriculture, and daily human life because they have essential loading capability. Many studies about path-tracking of wheeled mobile robots have been conducted. However, the path-tracking accuracy of these robots is low due to non-linear friction in the wheels, centre-of-gravity shifts and load changes. To address these issues, this paper proposes a motion control method based on the adaptive control law for a wheeled mobile robot. This control method does not need the exact values of plant parameters and can adapt to parameter uncertainties by measuring and adjusting the parameters automatically. Therefore, it is very robust to plant parameter changes caused by non-linear friction, centre-of-gravity shifts, and load changes. To verify the effectiveness of the proposed control method, path-tracking simulations are carried out. The simulation results demonstrate the feasibility and effectiveness of the adaptive control method.